Realizing Renewable Energy Storage Potential in Municipalities: Identifying the Factors that Matter - Dolge Kristiāna; Toma Annija Sintija; Grāvelsiņš Armands; Blumberga Dagnija (Environmental and Climate Technologies, 2023)
The share of renewable energy in heat and power generation is expected to increase significantly and reach record levels in the coming decades. As a result, emerging energy storage technologies will be key elements in balancing the energy system. To compensate the variability and non-controllability of seasonally generated renewable energy (RES) (daily fluctuations in solar radiation intensity, wind speed, etc.) development of sufficient energy storage infrastructure in the regions will play a major role in transforming RES supply potential into reality. However, local public authorities that are responsible for creating an enabling policy environment for RES infrastructure development in regions encounter numerous challenges and uncertainties in deploying sufficient energy accumulation that often remain unanswered due to a lack of knowledge and on-site capacity, which in turn significantly hinders the regional path to climate neutrality. In this study, the PESLTE analytical framework and composite index methodology is applied to examine the multidimensional factors that influence the deployment of renewable energy storage technologies in municipalities: political, economic, social, legal, technological, and environmental. Developed model is approbated in a case study in a Latvian municipality where four different alternative energy storage technologies are compared: batteries for electricity storage, thermal energy storage, energy storage in a form of hydrogen, and energy storage in a form of biomethane.